2014
DOI: 10.1074/jbc.m114.570077
|View full text |Cite
|
Sign up to set email alerts
|

Translation Elongation Factor 1A Mutants with Altered Actin Bundling Activity Show Reduced Aminoacyl-tRNA Binding and Alter Initiation via eIF2α Phosphorylation

Abstract: Background: Eukaryotic elongation factor 1A (eEF1A) interacts with the actin cytoskeleton. Results: Mutations in eEF1A that cause actin disorganization affect translation at both the initiation and elongation steps. Conclusion: Reduced aminoacyl-tRNA binding by eEF1A and increased eukaryotic initiation factor 2␣ (eIF2␣) phosphorylation are connected through Gcn2p. Significance: Alternative eEF1A functions can affect the interplay between translation steps and other cellular processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…eEF1A can also bind and bundle the actin cytoskeleton. Amino acid substitutions in eEF1A could cause improper actin organization in vivo and reduce total translation at the level of AA‐tRNA binding in vitro (Perez and Kinzy ). In addition, Belyi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…eEF1A can also bind and bundle the actin cytoskeleton. Amino acid substitutions in eEF1A could cause improper actin organization in vivo and reduce total translation at the level of AA‐tRNA binding in vitro (Perez and Kinzy ). In addition, Belyi et al .…”
Section: Discussionmentioning
confidence: 99%
“…eEF1A can also bind and bundle the actin cytoskeleton. Amino acid substitutions in eEF1A could cause improper actin organization in vivo and reduce total translation at the level of AA-tRNA binding in vitro (Perez and Kinzy 2014). In addition, Belyi et al (2009) had found that modifying EF1A at serine 53 by Lgt 1, produced by Legionella pneumophila, could lead to inhibition of protein synthesis and death of target cells.…”
Section: Discussionmentioning
confidence: 99%
“…The eEF1A mutant proteins, in particular the F309L and S405P mutants, reduced actin bundling in vitro, supporting the original biochemical data from the Condeelis laboratory (Yang et al 1990), and caused defects in the cell cytoskeleton and morphology, revealing a critical biological role for this interaction. Most surprisingly, these eEF1A mutants showed translation defects at the level of initiation and increased phosphorylation of eIF2a (Perez and Kinzy 2014). Deletion of the eIF2 kinase GCN2 eliminated the initiation defect, but revealed an elongation defect.…”
Section: Ribosomal Frameshiftingmentioning
confidence: 99%
“…It could do this by either impeding the binding of GCN2 to its substrate, eIF2α, or by preventing the complete intramolecular rearrangements of GCN2 required for the phosphorylation of eIF2α (Visweswaraiah et al, 2011). eEF1A binds to F-actin (Liu et al, 1996;Munshi et al, 2001), and in yeast, mutations in eEF1A that affect aminoacyl-tRNA binding simultaneously cause actin binding and/or bundling defects and increased phosphorylation of eIF2α dependent on GCN2 (Gross and Kinzy, 2007;Perez and Kinzy, 2014).…”
Section: Introductionmentioning
confidence: 99%